A systematic review and meta-analysis of cross-reactivity of antibodies induced by oil-in-water emulsion adjuvanted influenza H5N1 virus monovalent vaccines. Issue 24 (31st May 2017) - Chada, Kinnera E.; Forshee, Richard; Golding, Hana; Anderson, Steven; Yang, Hong
Highlights: Study evaluated cross-reactive neutralizing ability of OWEA H5N1 vaccine strains. OWEA H5N1 vaccines elicit cross-clade antibody responses against subclades 1 and 2. These vaccines may allow targeted outbreak control at the start of a pandemic. Abstract: Background: Cross-clade immunogenic stockpiled H5N1 vaccines may decrease the morbidity and transmission of infection during the initial phase of influenza pandemic. Meta-analysis of cross-reactive antibodies induced by oil-in-water emulsion adjuvanted (OWEA) influenza H5N1 virus monovalent vaccines with circulating heterologous H5N1 virus strains, isolated from human infections was performed. Methods: Literature search of MEDLINE, EMBASE, Web of Knowledge, The Cochrane Library, ClinicalTrials.gov, and International Standard Randomised Controlled Trial Number registry was conducted up through December 1, 2015. Methodologically qualified studies were included for (1) use of two doses of licensed OWEA (AS03 or MF59) egg-derived, inactivated influenza H5N1 virus monovalent vaccine, (2) participant age between 18 and 64 years, and (3) evaluation of immunogenicity outcome for one or more subclade. Meta-analysis assessed the cross-reactivity of antibodies elicited by clade 1 adjuvanted vaccine strain against clade 2.1 virus strain (A/Vietnam/1194/2004 vs. A/Indonesia/05/2005); and separately against clade 2.2 virus strain (A/Vietnam/1194/2004 vs. A/turkey/Turkey/1/05); and clade 2.1 adjuvanted vaccine strain against clade 1 virus strain (A/Indonesia/05/2005 vs. A/Vietnam/1194/2004). Quantitative publication bias and influence analysis was conducted to evaluate potential impact of unpublished or new studies on the robustness of meta-analysis. Results: Of 960 articles, 53 qualified for quality assessment and 15 studies met the inclusion criteria. All assessed clade pairs elicited cross-reactive antibodies (clade 1 against clade 2.1 and 2.2; clade 2.1 against clade 1, 2.2, and 2.3). Heterologous strains of same sub-clade are likely to elicit higher cross-reactive antibodies. Conclusions: OWEA influenza H5N1 virus monovalent vaccines exhibit broad cross-clade immunogenicity, a desired feature for vaccine stockpiling not yet demonstrated by unadjuvanted vaccines. In case of an impending H5N1 virus pandemic, stockpiled OWEA influenza H5N1 virus monovalent vaccines may allow population priming that could slow down the course of pandemic and could offer additional time needed for development of an effective strain specific vaccine supply.